PERAN MEDIASI MOTIVASI KERJA PADA GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA WYNDHAM GARDEN KUTA BEACH BALI) - Ni Nyoman Srutiningsih; Ni Luh Wayan Sayang Telagawathi; Trianasari Trianasari (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study was to determine the effect of transformational leadership style and work compensation on employee’s performance with work motivation as mediation at Wyndham Garden Kuta Beach Bali. The research method is descriptive causality using a quantitative approach. The sampling technique used is using non-probability sampling on employees in the guest contact department. Data collection technique by distributing questionnaires to 56 respondents. The data analysis technique used is a path test with the SmartPLS 3.0 Software analysis tool. The results showed that: (1) transformational leadership style has a positive and significant effect on employee performance, (2) work compensation has a positive and significant effect on employee performance, (3) work motivation has a negative and insignificant effect on employee performance, (4) transformational leadership style has a negative and significant effect on work motivation, (5) work compensation has a positive and significant effect on work motivation and (6) work motivation does not have mediating role either transformational leadership style nor work compensation on the employees performance of Wyndham Garden Kuta Beach Bali. Theoretically this research is providing the implications that work compensation is the main factor in improving employee performance. Practically, this research has implications for Wyndham Garden Kuta Beach Bali that there is an expectation of an increase in employee performance by giving attention to the aspects of leadership style, work compensation, and employee motivation.